Inflicted and Noninflicted Traumatic Brain Injury - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1998)
Neuroimaging, physical, and neurobehavioral findings after inflicted and noninflicted traumatic brain injury (TBI) in 40 children, 0 to 6 years of age, were compared in a prospective longitudinal study at the University of Texas at Houston Health Science Center, and Baylor College of Medicine, Houston, TX.